Experimental Investigation on Efficiency Factor of Pile Groups Regarding Distance of Piles - Mojtaba Pashayan; Gholam Moradi (Salehan Institute of Higher Education, 2019)
There are a lot of the parameters which affect pile group behavior in soil. One of these factors is the distance of piles from each other. The impact of distance on pile groups in sand has been investigated through some researches, whereas most of them have not represented an exact estimation according to the continuous change of the distance in sand. Moreover, most of previous investigations have considered two piles as a perfect group. Since two-pile group has the least interaction effect among piles, it cannot suitably demonstrate the influence of spacing. In this lecture, several 4-pile groups modeled with different spacing were subjected to axial loading in laboratory. The pile groups were free-head with length to diameter ratio of 13.5. The piles are designed in a way which the shaft resistance of piles can be completely mobilized through the test. Then, the bearing capacities of pile groups are measured and compared with the single pile's resistance in order to calculate the efficiency coefficient of the groups. It is revealed that the distance is noticeably effective in efficiency factor and this effectiveness, non-linearly decreases by increase of spacing. The results show that the efficiency coefficient is changing between almost 1 and 1.4.